Diagnostic Accuracy Of Tokyo Guidelines 2018, In Acute Cholecystitis, Taking Histopathology As Gold Standard - Rehman, Mujahid Ur; Dian, Asifa; Omer, Muhammad; Batool, Kanza; Ayoub, Adil; Zia, Naeem (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the diagnostic accuracy of the 2018 Tokyo Guidelines for acute cholecystitis by comparing clinical diagnosis with histopathological findings in patients undergoing cholecystectomy. Methods: This prospective observational study was conducted on 71 patients undergoing cholecystectomy with a preoperative diagnosis of acute cholecystitis based on TG18. The diagnostic criteria included clinical features (right upper quadrant pain, Murphy’s sign), laboratory parameters (leukocytosis, elevated CRP), and imaging findings on abdominal ultrasonography (gallbladder wall thickening, pericholecystic fluid). Postoperative histopathological examination of the resected gallbladders was used as the gold standard for confirming the diagnosis. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated. Results: Out of 71 patients, histopathology confirmed acute cholecystitis in 64 cases and ruled it out in 7. The Tokyo Guidelines demonstrated a sensitivity of 93.4%, specificity of 40%, positive predictive value of 90.47%, negative predictive value of 50%, and an overall diagnostic accuracy of 85.91%. Six patients had discordant results, showing false-positive diagnoses according to the Tokyo Guidelines, which were not supported by histopathology. Conclusion: The 2018 Tokyo Guidelines are highly sensitive and have good diagnostic accuracy for acute cholecystitis, making them valuable in clinical settings. However, the low specificity and modest NPV indicate a potential for overdiagnosis. Refinement of diagnostic criteria is warranted to reduce false-positive rates and improve the detection of true negative cases. Keywords: Acute Cholecystitis; Tokyo Guidelines; Diagnostic Accuracy; Cholecystectomy; Histopathology; Sensitivity and Specificity